Chunking in simultaneous interpreting: the impact of task complexity and translation directionality on lexical bundles - Huang, Dan Feng; Li, Fang; Guo, Hang (Frontiers in Psychology, 2023)
This study explored the use of phraseological frames (p-frames), a type of lexical bundle, by simultaneous interpreters as a strategy for managing cognitive loads. Specifically, using a comparable corpus of United Nations Security Council conferences, the study employed kfNgram to automatically identify the p-frames, and investigated their variations, regarding frequency, fixedness, structures, and functions among L1, L1–L2, and L2–L1 texts, which differ in cognitive loads due to task complexity and directionality of interpreting. The findings indicated that interpreters used more p-frames as cognitive loads increased; No significant difference was identified in fixedness as all texts tended to employ heavily formulaic and relatively fixed p-frames. Directionality correlated with grammatical preferences, with retour interpreting relying more on content-word-based p-frames. Additionally, task complexity correlated with functional preferences, with self-expression characterized by more stance expressions in the simple task. This study innovatively addressed the interaction of two factors that generate cognitive loads in interpreting and filled a research gap by providing empirical evidence on how directionality affects the use of formulaic language.